Effects of coal mining subsidence on the rhizosphere environment of Artemisia ordosica in Mu Us sandland, northwest China - Zhang Yanxu; Bi Yinli; Wang Zhigang; Qiu Lang; Sun Huan; Cai Yun (矿业科学学报, 2016)
Taking the rhizosphere soil ofArtemisia ordosica in Mu Us sandland as an example, the effects of soil physi-chemical properties, soil microorganism and enzyme activities after 1-3 years’ subsidence were analyzed.The results showed that soil bulk density and field capacity decreased, and rhizosphere soil available phosphorus, potassium and nitrogen content decreased significantly (P< 0.05) after subsidence, but soil pH and conductivity increased significantly compared with the un-disturbance area.The quantities of bacteria and actinomycetes decreased in the depth of 0-20 cm, while the quantities of fungi increased.As compared to the un-disturbance area, soil microbial quantity increased in the 20-40 cm and 40-60 cm layers.Soil acid phosphatase activity increased significantly after subsidence (P< 0.05).Soil invertase activity in the surface increased significantly after 2-3 years’ subsidence, while there was no significant difference in the deep soil (P> 0.05).There was no significant difference on soil available phosphorus and nitrogen, the quantities of bacteria in surface soil, soil urease and invertase activity between subsidence area and the un-disturbance area after 3 years.The rhizosphere environment of plants has a certain self-repair capacity, but it will take a long time to reach the level of nature eco-environment after mining subsidence.